Impact of English Language Proficiency on the Quality of Job Execution of Engineers in and outside Nepal: A Study at a Glance - Shrestha, Rup Narayan; Awasthi, Jai Raj; Pahari, Bharat Raj (Journal of the Institute of Engineering, 2020)
The present research article attempts to explore some facts about the importance of English language proficiency on the execution of engineering jobs all over the world in general and in Nepal in particular. Based mainly on the review of literature available in the internet and some other local resources, this paper highlights that English language proficiency is indispensable for the engineering graduates both outside and inside Nepal in the present day situation for the successful execution of engineering jobs. The findings reveal that mere technical knowledge about core engineering subjects may not suffice in the engineering area unless engineers are well-equipped with sufficient communication skills in English as engineering has inherent intimate relationship with English language as a medium worldwide.